TAFTA: fuelling trade discrimination or global liberalisation? - Horst Siebert; Rolf J. Langhammer; Daniel Piazolo (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
This paper analyses the prospects and problems of a Transatlantic Free Trade Area (TAFTA) between the European Union and the United States. Possible economic reasons for the proposal of TAFFA such as the intensity of bilateral trade and a strong interdependence in investment flows and the similarity of the EU and the US in their factor endowment and tariff structure are examined. There are cases shining favourably on the idea, but the implementation of TAFTA will imply substantial costs due to the internal and external consequences. The main problem of a free trade area between the two most important economic blocs is the impact on the multilateral approach of trade liberalisation. The authors suggest a Transatlantic Liberalisation Initiative (TALI) as an alternative to TAFTA. Under TALI, the EU and the US should accelerate their implementation of their Uruguay Round commitments and liberalise in areas that are not yet covered by WTO agreements. This should be done under the Most-Favoured Nation clause and would be a strong motivating force for multilateral liberalisation. In addition, TALI could be a forerunner in reducing market segmentation and in establishing a semiinternal market between Europe and America.
Keywords: F15; 330; Transatlantic Free Trade Area; regional integration; European Union; multilateral liberalisation; United States